The Spiritual Concept In The Lyric Of The Wengi Énjing Tepang Deui Song By Tatang Sastrawiria - Gardapandawa, Budi Setiawan; Alif, Mohamad Zaini; Suparli, Lili (UNIVERSITAS PAKUAN, 2025)
This research focuses on analyzing the meaning of the lyric of the Wengi Énjing Tepang Deui song by Tatang Sastrawiria using ideas from R.A Darja regarding pancacuriga. In analyzing the intertextuality contained in the meaning of the lyrics of the Wengi Énjing Tepang Deui song, this research was also elaborated with knowledge and understanding of Sundanese culture to obtain a comprehensive meaning. The results of this research show that the meaning constructed through the dictions and lines in the lyric of the Wengi Énjing Tepang song Deui song offers spiritual concept that are structured through the laku manekung which aims to gain enlightenment and become a true human being (Manusia Sejati). The meaning of this spiritual concept is obtained through concluding from the meanings that have been interpreted as sasmita or deeper meaning from the Wengi Énjing Tepang Deui lyric.